PENGARUH MODUL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUGMENTED REALITY BERBASIS KEARIFAN LOKAL GUSJIGANG TERHADAP PEMAHAMAN KONSEP IPA SD 3 BARONGAN: PENGARUH MODUL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUGMENTED REALITY BERBASIS KEARIFAN LOKAL GUSJIGANG TERHADAP PEMAHAMAN KONSEP IPA SD 3 BARONGAN - Nisrina Aufi Rahmaveira; Sekar Dwi Ardianti; Khamdun . (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The success of students in the learning process, especially through learning media, is measured by the results of students' understanding of concepts. Low understanding of science concepts in Energy Sources material for class 4 SD 3 Barongan. This research aims to find out whether Augmented Reality media based on GUSJIGANG local wisdom has an effect on the results of students' conceptual understanding and how much the results of students' conceptual understanding of science material at SD 3 Barongan have increased. This research uses a quantitative experimental method with a one group pretest-posttest design. This research used subjects from all class IV of SD 3 Barongan, totaling 15 students, using a non-probability sampling technique, a saturated sample type. Data collection takes the form of interviews, observations, tests (pretest and posttest), and documentation. Data analysis techniques include normality test, homogeneity test, paired sample t-test, N-Gain test. The results of this research show that the PBL model assisted by Augmented Reality media can provide differences in average scores and can improve students' conceptual understanding results. This statement can be obtained from the results of the paired sample T-Test and N-Gain test. In this test, the results of the paired sample T-Test were obtained with a significance of 0.000, which means Ho was rejected and Ha was accepted. Meanwhile, the N-Gain result was 69.2%, which means that increasing students' understanding of concepts can be categorized as quite effective Keywords: Augmented Reality, Local Wisdom, Concept Understanding